An energy efficient based hybrid clustering (EEBHC) approaches in wireless sensor network - Perumal, V; Meenakshi Sundaram, K (International Journal of Engineering and Technology, 2018)
Recently, much amount of research work has been carried out to improve the network lifespan in the Wireless Sensor Network (WSN) using Energy consumption process. In our proposed hierarchical based Hybrid clustering approaches has been designed, so as to limit the network traffic towards the Base Station. It reduced energy in the primary role of data transmission, reception, sensing and aggregation. To collect the data in the surrounding information based on hybrid clustering techniques. In this techniques are combination of equal and unequal Clustering. Even though equal and unequal clustering method is used to enable the routing of data to minimizes the power consumption in the WSN. The hybrid clustering techniques are used the Cluster Head (CH) selection process depending on higher energy level and routing efficiency of the network. The proposed works NS2 simulator is utilize the data from the source to destination in efficient way of using EEBHC algorithm to minimize the energy consumption, reduced traffic occurrences, avoid packet losses and extends the lifetime of network.Â